Laparoscopic cystogastrostomy in children with pancreatic pseudocysts: A preliminary experience of eight cases - Vivek Samuel Gaikwad; Sundeep M C. Kisku; Jujju Jacob Kurian; Tarun John K Jacob; John Mathai (Wolters Kluwer Medknow Publications, 2022)
Introduction: Pancreatic pseudocysts (PPCs) and walled-off necrosis (WON) in children following acute pancreatitis are uncommon. The various modalities of therapy possible are conservative treatment, external drainage, endoscopic stenting, and internal surgical drainage procedures. There are no existing guidelines for the management of PPC in children. We evaluate the outcomes of laparoscopic cystogastrostomy (LCG) performed at our center. Materials and Methods: Eight children (median age: 10 years) underwent LCG for large PPC (median size: 12.5 cm). There were seven patients with PPC and one with WON. Seven underwent LCG by a transgastric approach and one underwent LCG by a retrogastric approach. Results: Seven out of the eight patients had complete resolution of symptoms and the PPC. The median follow-up period was 32 months (interquartile range: 9.5-55.5 months). There were no conversions. There was one patient with a WON who developed a recurrence. Conclusion: LCG is a safe and effective treatment option for large PPC/WON in children. A posterior retrogastric approach, when indicated, is a safe approach with a comparable outcome.